Co-located quantitative trait loci mediate resistance to Agrobacterium tumefaciens, Phytophthora cinnamomi, and P. pini in Juglans microcarpa × J. regia hybrids. (1st May 2021) - Ramasamy, Ramesh K; Luo, Ming-Cheng; Leslie, Charles A; Velasco, Dianne; Ott, Natalia; McClean, Ali; Dandekar, Abhaya M; Aradhya, Mallikarjuna; Brown, Patrick J; Browne, Gregory T; Kluepfel, Daniel A; Westphal, Andreas; et al.
Abstract: Soil-borne plant pathogens represent a serious threat that undermines commercial walnut ( Juglans regia ) production worldwide. Crown gall, caused by Agrobacterium tumefaciens, and Phytophthora root and crown rots, caused by various Phytophthora spp., are among the most devastating walnut soil-borne diseases. A recognized strategy to combat soil-borne diseases is adoption of resistant rootstocks. Here, resistance to A. tumefaciens, P. cinnamomi, and P. pini is mapped in the genome of Juglans microcarpa, a North American wild relative of cultivated walnut. Half-sib J. microcarpa mother trees DJUG 31.01 and DJUG 31.09 were crossed with J. regia cv. Serr, producing 353 and 400 hybrids, respectively. Clonally propagated hybrids were genotyped by sequencing to construct genetic maps for the two populations and challenged with the three pathogens. Resistance to each of the three pathogens was mapped as a major QTL on the long arm of J. microcarpa chromosome 4D and was associated with the same haplotype, designated as haplotype b, raising the possibility that the two mother trees were heterozygous for a single Mendelian gene conferring resistance to all three pathogens. The deployment of this haplotype in rootstock breeding will facilitate breeding of a walnut rootstock resistant to both crown gall and Phytophthora root and crown rots.